Multi-drug resistant pathogenic Listeria monocytogenes in surface water and soil samples of Dhaka city - Manjur, Md Shifat E; Siddique, Shahariar; Ahmed, Sangita (Bangladesh Journal of Microbiology, 2018)
Listeria monocytogenes, the causative agent of human listeriosis is widely distributed in nature and a major threat to human health. Aiming to investigate the environmental distribution of this pathogen in Bangladesh, the current study conducted an initial investigation on 30 soil samples and 20 surface water samples for the presence of the pathogenic Listeria monocytogenes. Based on cultural, morphological, biochemical tests and presence of the virulent gene hly, 7 (14%) Listeria monocytogenes were obtained of which, surface water samples contained four Listeria monocytogenes (15%) while, three Listeria spp. (13.33%) were isolated from soil samples. Antibiotic resistance profile of the Listeria isolates showed that 100% isolates were resistant to erythromycin and resistance to oxacillin, ampicillin, sulphamethoxazole-trimethoprim and penicillin was 71%, 57%, 43% and 43% respectively. 71% Listeira monocytogenes isolates were sensitive to vancomycin and 100% sensitivity was observed to imipenem. This study shows that multi-drug resistant pathogenic Listeria monocytogenes is widely spread in soil and water samples in Dhaka and imposes great risk to public health. Bangladesh J Microbiol, Volume 33, Number 1-2, June-Dec 2016, pp 39-42